Correlations in Leaf Chlorophyll and Yield Related Traits of Dry Bean (Phaseolus vulgaris L.) - Guler, Semiha (Asian Journal of Chemistry, 2010)
The aim of the present study was to investigate correlations between leaf chlorophyll, yield and yield contributing characters in dry bean. Six dry bean lines and 4 cultivars were evaluated in terms of leaf chlorophyll, seed yield, 100 seed weight (100 seed weight), pod number per plant, seed number per plant, seed number per pod, harvest index and plant height. Except for leaf chlorophyll and harvest index, there were significant differences among cultivars in relation to investigated traits. There were significant correlations between seed yield and pod number per plant (r = 0.727, p < 0.05), seed yield and seed number per plant (r = 0.831, p < 0.01), seed yield and harvest index (r = 0.718, p < 0.05), pod number per plant and seed number per plant (r = 0.925, p < 0.01) and seed number per plant and seed number per pod (r = 0.702, p < 0.05). Path coefficient analysis revealed that pod number per plant (0.9873), 100 seed weight (0.7209) and seed number per pod (0.4762) had significant direct effect on seed yield. Although leaf chlorophyll had a small direct effect on seed yield, it had substantial indirect effect via 100 seed weight. The study revealed that the dry bean lines and cultivars having the lowest leaf chlorophyll reading value taken at 38 d after emergence is not a sign for poor yield. The highest chlorophyll reading value taken at that stage does not warrant for higher yield.